A Girardian Reading of Schmitt's Political Theology - Palaver, Wolfgang (Telos, 1992)
One of the more intriguing things in Carl Schmitt's Political Theology (1922) is the parallels he draws between Thomas Hobbes (1588-1679) and Juan Donoso Cortés (1809-1853). According to Schmitt both are representatives of decisionism: "Donoso Cortes, one of the foremost representatives of decisionist thinking and a Catholic philosopher of the state … concluded in reference to the revolution of 1848, that the epoch of royalism was at an end. Royalism is no longer because there are no kings. Therefore legitimacy no longer exists in the traditional sense. For him there was thus only one solution: dictatorship. It is the solution that Hobbes also reached by the same kind of decisionist thinking, though mixed with mathematical relativism. Autoritas, non veritas facit legem."